저작권법상 패러디에 관한 일 고찰 - 계승균(Kye Seung-Kyoon) (Tonga pŏphak, 2012)
패러디는 저작권법상 다양한 논점을 제시하고 있다. 왜냐하면 패러디는 기존의 저작물의 핵심적인 부분을 다루면서도 저작권침해가 성립되지 않기 때문이다. 기존의 법리에 따르면 타인의 저작물의 창작성이 가장 뛰어난 부분에 대한 변형을 가하기 때문에 직접적인 저작권침해가 성립되어야 하지만, 패러디는 오히려 저작권침해가 부정되고 새로운 창작물로서 칭송을 받으며 새로운 저작권을 창출하는 것이다. 이에 대한 논리적 법리적 근거가 무엇인지에 관해서 계속하여 논의가 이루어지고 있다. 우리나라 판결의 경우 아직 패러디에 대한 인정을 정면으로 다룬 사안은 없어 보이지만 아직은 보수적으로 생각하고 있다고 보인다. 창작환경의 변화는 패러디를 촉진시키고 있다. 그렇지만 표절이나 다른 사람의 저작물을 적당히 옮기면서 패러디라고 주장할 가능성도 높다. 따라서 이에 대한 구분 내지 명확한 기준을 제시하는 것은 사실상 어려운 일이라고 판단되지만, 미국이나 일본, 독일 등의 사례와 이에 대한 법리적 분석 등을 통하여 하나씩 해결이 가능하다고 본다. 또한 패러디는 저작권법상의 2차적저작물, 인용조항, 동일성유지권, 공정이용, 표절 등 다양한 논점들과 부딪치고 있다. 사실 패러디를 정당화시키기 위해서 근거로 제시되고 있는 법리들의 요건을 살펴보면 패러디의 정당화를 근거지우기에는 다소 부족한 면이 있었다. 그래서 인용조항이 가장 패러디정당화에 가까운 조항이라고 판단하여 왔다. 그러나 저작권법개정을 통해 미국의 공정이용조항을 도입하여 앞으로는 이 조항에 따라 패러디에 대한 법리적 심사가 이루어질 가능성이 높아졌다. 패러디가 활성화 되도록 하는 것도 문화창달을 위한 한 방편이라는 점에서 패러디에 관한 법리적 분석과 함께 비교법적인 고찰이 지속적으로 이루어져야 한다. This paper is devoted to examining a parody from the viewpoint of legal perspective, especially centering around the Korean Copyright Law. A parody is one of the important arguing points in the copyright law of each nation, because it has many issues related to the author's moral rights and author's property rights of copyright. In addition, a parody is the most important example to show the difference between copyright and patent as well as trademark. To borrow the core contents in the protected original works of others is the clearest character which is not criticised by the author of original works. It is praised by the public, meaning means legal and new creative works, which is qualified to be protected by copyright law. However, if a man use the core contents of patented invention and protected trademark, it is considered a direct infringement under the Korean Patent Act or Trademark Act. I think that the most similar concept to parody is a plagiarism which is taking the words or expressions protected by law from other's works and use as his own without admitting one has done so. The plagiarist has a tendency to insist that his works are a parody that means original and creative works. Even though the creative structure between parody and plagiarism is similar, the direction or effect of each one is thoroughly different. According to the Korean Copyright Act that was revised in last year, parody is anticipated to be subject to the Fair Use Clause that has recently added. This Clause was developed over a hundred years ago in the American Copyright Law with many cases. KCI Citation Count: 10